The SarcoEndoplasmic Reticulum Calcium ATPase (SERCA) pump: a potential target for intervention in aging and skeletal muscle pathologies - Hongyang Xu (BMC, 2021)
Abstract As a key regulator of cellular calcium homeostasis, the Sarcoendoplasmic Reticulum Calcium ATPase (SERCA) pump acts to transport calcium ions from the cytosol back to the sarcoplasmic reticulum (SR) following muscle contraction. SERCA function is closely associated with muscle health and function, and SERCA activity is susceptible to muscle pathogenesis. For example, it has been well reported that pathological conditions associated with aging, neurodegeneration, and muscular dystrophy (MD) significantly depress SERCA function with the potential to impair intracellular calcium homeostasis and further contribute to muscle atrophy and weakness. As a result, targeting SERCA activity has attracted attention as a therapeutical method for the treatment of muscle pathologies. The interventions include activation of SERCA activity and genetic overexpression of SERCA. This review will focus on SERCA function and regulation mechanisms and describe how those mechanisms are affected under muscle pathological conditions including elevated oxidative stress induced by aging, muscle disease, or neuromuscular disorders. We also discuss the current progress and therapeutic approaches to targeting SERCA in vivo.